Social studies of technology: an analysis of the theme on the publication production in Brazil and in the USA - Böck, Bruno Stefoni (2016)
The present study aims to identify research themes that concern the issue of technology in internationaljournals focusing on social studies of science and technology and in STS publications in Brazilian journals of education. For this purpose, articles that address the technology theme were collected. In the Brazilian case, the survey showed that only 13 of the collected articles were related to the subject under consideration, which invalidated the creation of a keywords network. For the international journals research, the Social Studies of Science magazine was mapped. 77 articles on technology were collected which generated a network of 373 keywords and led to the identification of the most relevant ones. The countries, institutions and fields of all publications’ authors were also submitted to analysis.